Eksplorasi Faktor Kunci Dalam Diri Karyawan: Implikasi terhadap kinerja karyawan dalam pendekatan Tinjauan Literatur - Maulina, Dwi; Hafizh , Abdul; Cipta, Agung Budi; Amirun, Aldino Arief (Universitas Ibn Khaldun Bogor, 2024)
In an increasingly competitive era of globalization, organizations need to understand the internal factors that influence employee performance to develop effective strategies for enhancing productivity and work quality. The research method used is a literature review, analyzing 15 selected articles based on specific inclusion criteria. The results indicate that a positive self-concept is closely related to better employee performance. Additionally, personal values and individual behavior also significantly influence employee performance. In various sector contexts, this research highlights the importance of building a positive self-concept among employees to enhance organizational productivity and efficiency. Further research is needed to understand the complex relationship between these internal factors and employee performance, as well as to apply these findings specifically in various organizational contexts. Overall, this study demonstrates that a better understanding of self-concept, personal values, and individual behavior can assist management in developing more effective strategies to improve employee performance and achieve organizational goals.